Analysis of the Relationship between Digital-Based Work-Life Integration and Turnover Intention among Young Workers in Indonesia within the Context of Modern Work Transformation - Januaria, Maria; Putri, Kesya; Zahara, Adinda Putri (Universitas Sains dan Teknologi Komputer, 2025)
The rapid advancement of digital technology has fundamentally transformed how young workers in Indonesia engage with their professional activities. Modern, digitally integrated work environments offer greater flexibility but also lead to psychological strain due to blurred boundaries between work and personal life. Grounded in this context, this study aims to analyze the relationship between digital-based work-life integration and turnover intention among young Indonesian workers, considering the mediating roles of work-life balance and digital work stress. The research employed an explanatory quantitative approach involving 250 respondents across sectors such as technology, digital finance, online education, and the creative industry. Data were collected through an online Likert-scale survey and in-depth interviews to complement the quantitative findings. The results indicate that digital work-life integration positively influences digital work stress and has a significant relationship with turnover intention, while work-life balance mitigates this effect. This study contributes theoretically by expanding understanding of digital integration dynamics among young workers and provides practical implications for organizations to design retention strategies aligned with the realities of flexible, technology-based work environments.